The Survey of Divorce Incidence in Divorce Applicants in Tehran - Jafar Bolhari; Fatemeh RamezanZadeh; Nasrin Abedininia; Mohammad Mahdi Naghizadeh; Hajar Pahlavani; Mehdi Saberi (Tehran University of Medical Sciences, 2012)
Objective: To study the qualification of divorce main factors so that it would be clarified proper consultation-intervention solutions to decrease it by counseling methods in the courts and counseling clinics. The divorce is categorized as the most tragic of social phenomenon, the damages and problems of which undergone by the couple and their families before and after divorce and the effective factors of this phenomenon incidence have been studied for many years. Divorce has different factors and it can never clarify a specific one as the main factor of divorce. Materials and methods: This survey studied the divorce creating factors in divorce applicants in Tehran Family courts (Shahid Mahalati-Vanak) during 2010-2011. The applicants of sampling group were including 300 referred ones from the courts, and the research method was descriptive and cross-sectional accomplishing by structured interview. Findings were shown as frequency and percent. Results: The results showed that the important factors of divorce request are including in order of psychic factors (93.3%), social and cultural factors (87.3%), sexual factors (88%), economical factors (80.3%), and violence (84.3%), and it may be  multi-factors as well. Conclusion: In addition to recommendation for more study in these fields, the results of this survey suggest to apply the necessary programming in teaching and counseling before the marriage as well as the necessity of informing the couple in receiving professional consults in time of problem incidence and proceeding for divorce in order to prevent from divorce incidence.